Relationship between overweight, physical activity and physical fitness in school-aged boys in bogotá colombia (2008)
The objective was to determine the prevalence of overweight and obesity, and its association with physical activity and fitness among boys attending a private school in Bogotá, Colombia. 655 boys between 7 and 18 years self-reported their physical activity habits and underwent anthropometric (weight, height, fat percentage by bioelectrical impedance), and physical fitness measurements (PACER, sit and reach, curl-ups, push-ups and hand dynamometry). The association between weight status and physical activity and fitness were assessed by logistic regression models. The outcome was that 38% of the boys were overweight according to the BMI of the Colombian population (WHO criteria), 17,7% according to international BMI cut-offs and 16,9% showed values of % fat over 25 (Fitnessgram criteria). A relation was found between being overweight and having poor performance in the aerobic fitness test (adjusted OR: 3,7, IC 95%:1,6-8,3) and reported not walking or riding a bicycle for at least 30 minutes, 5 times a week (OR adjusted 3,6, IC 95%: 1-13,0). These results did not change when different criteria to define overweight was applied. The best level of agreement for overweight classification was found between fat percentage and the international BMI cut-offs (kappa=0,616, p less than 0.001). Overweight was not associated to TV watching time, video games or use of Internet. The final conclusion was that the prevalence of overweight was high in this population of school-aged boys. There was a significant relationship between poor physical fitness, low levels of physical activity, and overweight. It is important to encourage and monitor children's levels of physical activity as well as the results of fitness test for the prevention of overweight and related cardio-metabolic complications.